Digital Capitalism - Fábics, István (Public Finance Quarterly, 2025)
Digital capitalism is one of the most defining socio-economic phenomena of our time, fundamentally reshaping our lives. Zoltán Pogátsa’s book *Digital Capitalism* (2024, ISBN 978-963-636-188-4) offers a comprehensive overview of how technological development has become the driving force of global capitalism and how it affects the economy, society, and the everyday lives of individuals. The book simultaneously presents the challenges and opportunities of the digital era, while providing an in-depth analysis of the socio-economic impacts of technological innovation. Pogátsa’s work touches not only on economic but also on social and ethical issues essential for understanding the digital future. The book addresses the topic across six chapters.